Optimalisasi pencegahan dan penanggulangan stunting di Desa Sungai Tuan Ilir - Any Zahrotul Widniah; Taufik Hidayat; Annisa Febriana (INDRA: Jurnal Pengabdian kepada Masyarakat, 2022)
Stunting is one of the chronic nutritional problems which is still an important problem in Indonesia. Lack of nutritional intake in the first 1000 days of life or lack of nutritional intake for a long time is the main cause of stunting. Indonesia is one of the developing countries with more than half the number of children experiencing stunting. The prevalence of stunting is in position 115 out of 151 countries in the world. Banjar Regency is ranks third out of 13 regencies/cities in South Kalimantan which is children experiencing stunting at 48.2%. Through community service activities by conducting stunting prevention and control programs is hoped that there will be an increase in community knowledge and attitudes in the family environment. The focus targets of this community service activity are families who have children under five and or couples of childbearing age in Sungai Tuan Ilir Village. The program is carried out in three stages, namely providing health education, interpersonal communication (KAP), and stunting prevention campaigns. The activities were carried out well according to the program planning that was made as evidenced by the increase in community knowledge and attitudes both during the mass counseling process and during KAP activities and stunting prevention campaigns in the family sphere.